MEMORY FOR COMPONENT DIMENSIONS OF VISUAL PATTERNS IN A SERIAL RECOGNITION TASK - Rosel Remírez, Jesús; Miranda, Jesús; López, Jesús (Anales de Psicología / Annals of Psychology)
A serial recognition experiment was conducted in which six images were presented in sequence (selected randomly from a total of 128 which could be generated by the combination of seven dimensions with two categories each). It was demonstrated that the subjects correctly remember only a few complete visual patterns; but an analysis of the number of correct answers for the variables of each image shows that: a) a significantly high number of categories in all the dimensions are remembered correctly; b) there are significant differences between the number of correct answers for the dimensions (the means of the number of categories correctly remembered in the different dimensions are very high, but differ amongst themselves, the order of recognition being: line, form, position, quantity, colour, width, and length); c) there are no significant differences according to sex.These results suggest that a great deal of information is recalled, and that the memory is selective, remembering the component variables of a visual pattern in different ways, which would confirm the model of the dependence of the recognition memory on visual patterns rather than more complex cognitive processes.